Association between BMI and periodontitis in women living with or at risk for HIV. (13th March 2022) - Janorkar, Deepti A.; Long, Dustin M.; Weber, Kathleen M.; Sharma, Anjali; Lin, Guo‐Hao; D'Souza, Gypsyamber; Edmonds, Andrew; Kassaye, Seble; Lahiri, Cecile D.; Konkle‐Parker, Deborah
Abstract: Aims: Currently, there is no data available assessing the association between body mass index (BMI) and periodontitis among women living with HIV (WLWH). This study aims to investigate this association among WLWH and women at risk for HIV (WRH) in the United States. Methods and results: Data from 351 WLWH and 52 WRH participants from the Women's Interagency HIV Study having pocket depths and clinical periodontal attachment loss assessments in 2003–2004 were included. Multinomial logistic regression analyses in the full sample assessed the relationship between BMI (underweight/normal, overweight, or obese) and periodontitis by severity (mild, moderate, severe), adjusting for study sites, age, education, annual household income, smoking, alcohol consumption, and diabetes. Overall, 75.2% women (76.0% WLWH; 69.0% WRH) had periodontitis. Moreover, 75.0% obese and 75.3% overweight women were affected by periodontitis. In the full sample, adjusted odds ratio (aOR) of having mild, moderate, and severe periodontitis in obese women were: 1.14 (95% confidence interval [CI]: 0.51–2.52), 1.02 (95% CI: 0.46–2.29), and 0.24 (95% CI: 0.06–1.07), respectively, and in overweight women: 0.70 (95% CI: 0.31–1.58), 0.85 (95% CI: 0.38–1.90), and 0.31 (95% CI: 0.08–1.15), respectively. Conclusions: Even with high prevalence of periodontitis among women with or without HIV infection in this cohort, this study does not provide evidence of an association between BMI and periodontitis.